2017
DOI: 10.3390/met7070271
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Investigation of Strain-Induced Martensitic Transformation Kinetics in an Austenitic Stainless Steel by Inductive Measurements

Abstract: An inductive sensor developed by Philips ATC has been used to study in-situ the austenite (γ) to martensite (α) phase transformation kinetics during tensile testing in an AISI 301 austenitic stainless steel. A correlation between the sensor output signal and the volume fraction of α-martensite has been found by comparing the results to the ex-situ characterization by magnetization measurements, light optical microscopy, and X-ray diffraction. The sensor has allowed for the observation of the stepwise transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The formation of martensite can be detected and evaluated by X-ray diffraction (XRD) [53,[78][79][80][81], neuron diffraction [82,83], electron backscatter diffraction (EBSD) [18,[84][85][86][87], magnetic methods including the eddy current method [88][89][90][91][92][93][94][95], metallography [78,89,96], and other techniques [96][97][98][99][100]. Some of these methods are briefly discussed in the following.…”
Section: Measuring Martensite Contentmentioning
confidence: 99%
“…The formation of martensite can be detected and evaluated by X-ray diffraction (XRD) [53,[78][79][80][81], neuron diffraction [82,83], electron backscatter diffraction (EBSD) [18,[84][85][86][87], magnetic methods including the eddy current method [88][89][90][91][92][93][94][95], metallography [78,89,96], and other techniques [96][97][98][99][100]. Some of these methods are briefly discussed in the following.…”
Section: Measuring Martensite Contentmentioning
confidence: 99%
“…However, beyond the depth of approximately 225 lm, almost no deformation-induced a 0 -martensite was detected in the optical microsections. a 0 -martensite content determined by image processing on the optical microsection shows only an approximation because the preparation process may also contrast slip and shear bands as well as emartensite, which may have caused an overestimation [64]. While it was difficult to determine the exact phase fractions, nevertheless, this method allowed estimations to be made about a 0 -martensite distribution in the workpiece surface layer.…”
Section: Metallurgical Propertiesmentioning
confidence: 99%
“…The The martensite phase is revealed in dark colors and the austenite is unetched. Parallel slip bands appeared in those grains that are favorably oriented with respect to the applied stress direction, where slip bands are localized crystallographic slip and, thus, cannot cross existing interfaces into other orientations [23]. It was indicated that the pointing process of the RSPM causes the strain-hardening, and the austenitic microstructure transforms to strain-induced α'-martensite phases during plastic deformation.…”
Section: Feasible Pointing Size For a Bar Pointing Turning Machinementioning
confidence: 99%